Heparin hydrogel sandwich cultures of primary hepatocytes. (November 2015) - Foster, Elena; You, Jungmok; Siltanen, Christian; Patel, Dipali; Haque, Amranul; Anderson, Leif; Revzin, Alexander
Graphical abstract: Highlights: Heparin-containing hydrogel used as sandwich-type scaffold for cultivation of functional primary hepatocytes. Gel layers fabricated via UV-induced thiol-ene coupling reaction of thiolated heparin (Hep-SH) and diacrylated poly(ethylene glycol) (PEG-DA) precursors. Heparin-binding hepatocyte growth factor (HGF) was retained in gel and promoted long-term cell functionality. Gel sandwich proven an excellent system for maintaining differentiated, polarized primary hepatocytes for over 3 weeks. Abstract: Long-term in␣vitro maintenance of primary hepatocytes has been a challenge in hepatic tissue engineering, since these cells dedifferentiate and lose their phenotype in standard culture conditions. Some of the most successful culture systems employ collagen or Matrigel matrices. As an alternative matrix, our laboratory has been exploring the use of heparin-containing hydrogels as scaffolds for cultivation of functional hepatocytes. The present study characterized a heparin gel sandwich culture system for maintenance of primary rat hepatocytes. The heparin gel layers were fabricated via UV light induced thiol-ene coupling reaction of thiolated heparin (Hep-SH) and diacrylated poly(ethylene glycol) (PEG-DA) precursors. Analysis of hepatic function revealed that cells sustained albumin secretion for at least three weeks at similarly high levels for collagen and heparin gel sandwich culture systems. Furthermore, cytochrome P450 activity of hepatocytes was ∼1.6 times higher in heparin gels compared to collagen gels. Another distinct advantage of heparin is its ability to bind and release growth factors in a controlled manner. We observed that after 24 days hepatocytes cultured in heparin gel sandwich containing hepatocyte growth factor (HGF) produced ∼1.8 times higher amounts of albumin compared to cells in collagen sandwiches. Overall, we demonstrate heparin gel sandwich to be an excellent system for maintaining differentiated, polarized primary hepatocytes for over three weeks. The biomaterial used in this study, heparin–PEG hydrogel, offers significant flexibility in terms of tuning mechanical properties, adjusting heparin content or introducing photolabile chemistries to promote gel degradation. We see multiple applications for this novel system in hepatocyte maintenance and stem cell differentiation studies.